An Ayurvedic Approach to Generalized Anxiety Disorder: A CaseStudy - Deepika; Singh , Naimish Raj; Varsakiya, Jitendrakumar Nathabhai; Anita Yadav (International Research Journal of Ayurveda & Yoga, 2025)
Generalized anxiety disorder is a common and disabling disorder characterized by persistent worrying, anxiety symptoms, and tension about a variety of everyday problems for a period of at least 6 months. The symptoms of this disease show resemblance with the Chittodwega ( excited state of mind) which is one among the Manovikara ( mental disorders) explained in Ayurvedic texts. According to the World Health Organization, the estimated prevalence of generalized anxiety disorder is 4%. Generalized anxiety disorder is diagnosed twice as frequently in women as men. To address this issue and reduce the need for allopathic medications with their potential adverse effects, an approach based on Ayurvedic principles is beneficial. A 53-year-old female patient came to the outpatient department of Kayachikitsa presented with complaints of insomnia, sudden feeling of warmness and coldness, giddiness, headache, burning chest, overthinking and negative thoughts, tinnitus, discomfort in crowded places, intolerance of loud noise, and constipation. The treatment protocol implemented during the patient’s first visit involved only Shamana Chikitsa ( pacifying therapy) including Anulomana ( promoting downward movement of doshas), Deepana ( appetizer), Pachana ( digestive), and Medhya ( nootropic) drugs. The patient was assessed for improvement in signs and symptoms after 1.5 months of treatment. The patient got significant relief in all symptoms. The Hamilton Anxiety Scale scores 29 before the treatment, later reduced to 09 after the follow-up. The present case study highlights the potential of Ayurveda intervention in the management of anxiety disorders.